Assessment of single-nucleotide variant discovery protocols in RNA-seq data from human cells exposed to mycotoxins. (24th March 2023) - Alonso-Garrido, M.; Lozano, M.; Riffo-Campos, A. L.; Font, G.; Vila-Donat, P.; Manyes, L.
Abstract: Food and feed contamination by nonlegislated mycotoxins beauvericin (BEA) and enniatin B (ENB) is a worldwide health concern in the present. The principal objective of this work is to assess some of the existing protocols to discover the single nucleotide variants (SNVs) in transcriptomic data obtained by RNA-seq from Jurkat cells in vitro samples individually exposed to BEA and ENB at three concentration levels (1.5, 3 and 5 µM). Moreover, previous transcriptomic results will be compared with new findings obtained using a different protocol. SNVs rs201003509 in BEA exposed cells and the rs36045790 in ENB were found in the differentially expressed genes in all doses compared to controls by means of the Genome Analysis Toolkit (GATK) Best Practices workflow. SNV-RNA-seq complementary pipeline did not show any SNV. Concerning gene expression, discrepant results were found for 1.5 µM BEA exposed cells compared with previous findings. However, 354 overlapped differentially expressed genes (DEGs) were identified in the three ENB concentrations used, with 147 matches with respect to the 245 DEGs found in the previous results. In conclusion, the two discovery SNVs protocols based on variant calling from RNA-seq used in this work displayed very different results and there were SNVs found manually not identified by any pipeline. Additionally, the new gene expression analysis reported comparable but non identical DEGs to the previous transcriptomic results obtained from these RNA-seq data. Graphical Abstract: UF0001 Single-nucleotide variants discovery protocols in transcriptomic data by RNA-seq from Jurkat cells exposed to mycotoxins for the first time